The impact of school-based continuing professional development: views of teachers and support professionals. Issue 3 (2nd July 2016) - de Paor, Cathal
Abstract : Evaluating the impact of school-based continuing professional development (CPD), as with any other kind, is not without its challenges. This article reports on an evaluation of a CPD programme which was established to support implementation of a new primary school curriculum in Ireland. It examines what can be learned by comparing the views on the likely impact held by the teachers participating in the CPD and the support professionals providing it. The results show that both groups were very positive about the likely impact. However, support professionals anticipated a greater impact than the teachers themselves on teachers' knowledge and implementation of the new curriculum. Likely explanations for these divergent views are discussed. The article highlights the importance of building in mechanisms within CPD to enable both teachers and support professionals to consider together the impact on an ongoing basis, and to use the available evidence formatively to inform planning for CPD. Incorporating a focus on impact in CPD is likely to become even more important in the years ahead given that teachers themselves are increasingly playing a greater role in decisions about what CPD is undertaken.